Sosialisasi Dampak Pernikahan Dini dan Penguatan Mental Remaja sebagai Strategi Pencegahan Pernikahan Dini - Purnami, Fasih Anggit; Maula, Dinda Minkhatul; Nisa, Aldha Aulia; Cahyaningtyas, Retno; Jundan, Ahmad Roid; Fitri, Fitri (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The rise of early marriage cases is a phenomenon that should be considered. Socialization of early marriage prevention is a preventive measure as an effort to reduce the number of early marriages. The purpose of the socialization is to raise awareness about the impact of early marriage which tends to be negative and detrimental. The method used is by applying service learning. Teenagers who are the target of this socialization are given counseling and understanding of early marriage and the various impacts and factors that can cause it to occur. The results include facts about early marriage that occur in the community, as well as changes in adolescents' views on early marriage. The impact of early marriage is the lack of knowledge about the importance of reproductive health, ignorance of married life that requires not only physical readiness but also mental, financial, and mature age. The conclusion confirms that early marriage has a detrimental impact so prevention of this phenomenon should be a serious concern for the future of the younger generation for the better.